Micronuclei formation in rainbow trout cells exposed to multiple stressors: Morpholine, heat shock, and ionizing radiation. (March 2018) - Sreetharan, Shayenthiran; Thome, Christopher; Tsang, Kara K.; Somers, Christopher M.; Manzon, Richard G.; Boreham, Douglas R.; Wilson, Joanna Y.
Abstract: Discharges from industrial cooling water systems can include low levels of morpholine (a chemical pH regulator and corrosion inhibitor), as well as transiently higher temperature effluent water which present a potential source of environmental impact to aquatic biota. The effects of environmental levels of morpholine or heat shock (HS) treatment alone and in combination with a challenge high-dose of 137 Cs ionizing radiation were studied using the cytokinesis block micronucleus assay in a rainbow trout cell line (RTG-2). Morpholine treatment of 10 or 100 mg L − 1 alone produced no significant effects, and no interaction was observed in combination with 7.75 Gy radiation. A 9 °C magnitude HS treatment alone significantly increased micronuclei formation. A synergistic response was observed when 9 °C HS was combined with 7.75 Gy radiation, with 15% more cells containing 3 or more micronuclei than the sum of each individual stressor. A synergistic increase in the average number of micronuclei was observed when morpholine and a 9 °C HS were co-treated. These results indicate that morpholine at environmentally-relevant levels does not impact micronuclei formation or cell cycle progression however 9 °C HS may be of potential concern both alone and in combination with other stressor treatments. Highlights: Micronuclei formation in RTG-2 cell line exposed to multiple stressors was studied. Morpholine at environmentally-relevant levels produced no significant responses. A heat shock of 9 °C resulted in significant micronuclei formation. Synergistic interactions with 9 °C heat shock and high-dose radiation observed